Medical Facilities for Refugees in Europe: Creating a Consultation for Resettled Syrian Families - Nahema El Ghaziri (Frontiers Media S.A., 2021)
The wave of migration that has hit Europe in recent years has led to several changes in the organization of asylum systems and medical care provided to migrants. Previous studies indicate that asylum seekers and refugees face multiple barriers in accessing health care. For that reason, adapted structures are needed. In this context, a family consultation service was implemented in our medical center in Lausanne, Switzerland. It aimed at addressing the unique health care needs of recently resettled families from Syria, which has been the leading source country for refugees since 2014. This intervention, developed through collaboration between the University Center for Primary Care and Public Health (Unisanté) and the Children's Hospital of Lausanne (HEL) involved a multidisciplinary team comprising a pediatrician, a general practitioner and a pediatric nurse. Bringing together a multidisciplinary team optimized care coordination, facilitated communication between care providers and enabled a more global vision of the family system with the aim of enhancing quality of care.